Mineral Trioxide Aggregate Mixed with Normal Saline, Calcium Chloride or KY Jelly as Apical Plug in Simulated Open Apices: An In vitro Microleakage Study - Mehrvarzfar, Payman; Akhavan, Hengameh; Ghasemi, Sara; Khodaei, Fatemeh; Savadkouhi, Sohrab Tour; Dianat, Omid (Iranian Endodontic Journal, 2013)
Introduction: Mineral trioxide aggregate (MTA) mixed with normal saline has short working time, delayed setting time, and poor consistency when used as an apical plug. A preliminary study suggested that substituting normal saline with KY Jelly or 5% calcium chloride (CaCl2) as a vehicle expedites the setting time of MTA. The present in vitro study compared the microleakage of ProRoot MTA mixed with normal saline (MS) to that of ProRoot MTA mixed with KY Jelly and/or 5% CaCl2 in simulated canals with open apices. Materials and methods: Thirty six single-rooted extracted human teeth were cleaned and shaped with ProTaper rotary system to make 36 standardized artificially created open apices. Teeth were randomly divided into three experimental groups (n=10) and two control groups (n=3). In group 1, MTA was mixed with normal saline (MS) and placed into the canals to form 4 to 5 mm apical plugs. In group 2, MTA was mixed with 5% CaCl2 (MC) and in group 3, MTA was mixed with KY Jelly (MK). The other two groups served as positive and negative controls. The remaining canal spaces in the experimental groups were backfilled with thermoplasticized gutta-percha without sealer. Dye penetration and clearing was used to evaluate the sealing ability of each group. The samples were then examined under stereomicroscope to measure the microleakage of different MTA mixtures in mm. Data were statistically analyzed using One-Sample Kolmogorov-Smirnov test for determination of normal distribution and then by one-way ANOVA and Tukey’s tests to detect any significance. Results: Positive and negative controls responded as expected. The MS group showed the least mean dye penetration value. There was a significant difference between MS with other groups (P<0.05) but no difference was found between MC and MK groups. Conclusion: Within the limitations of this in vitro study, we can conclude that among these three vehicles, normal saline mixed with ProRoot MTA has the least amount of microleakage in canals with open apices.